Farmers’ adaptation practices in climate-stressed coastal Bangladesh: a systematic review - Md Ashik Ur Rahman; Sadhon Chandra Swarnokar; S M Nayem Ahasan; M Mohibbullah; Sadia Islam Mou; Animesh K Gain (Environmental Research Communications)
Climate change poses serious threats, making it crucial to develop strong adaptation strategies. This is especially true in Bangladesh, where agriculture, the backbone of the economy, is highly vulnerable. Local communities in Bangladesh have used Indigenous knowledge and practices to adapt, but there is a lack of systematic examination of these strategies. In this study, we review literature from Web of Science, ScienceDirect, Scopus, and Google Scholar using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We identify various adaptation strategies grouped into six main themes and twenty-six sub-themes: crop management, water management, farm management, financial management, social adaptation, and traditional/local knowledge use. Diversifying income sources stands out as a key strategy against climate challenges. However, most strategies are short-term, reactive, and lack long-term sustainability. Our study highlights the importance of local adaptation strategies and questions their integration into national and regional development plans. The dominance of foreign-funded projects in publishing research shows the vital role of international collaboration in improving research quality and global knowledge exchange. The findings are relevant for regions where coastal agriculture is vital but impacted by climate change, including countries in Asia-Pacific, Africa, and South America.